Drawing the Line : Public and Private in America - Stark, Andrew, 1956- (Book collections on Project MUSE., 2010)
With the growth of the U.S national government under the Obama administration, the perennial debate over where to draw the line between public and private has come to the fore yet again. This time around, however, the stakes are higher than ever as unprecedented amounts of public money are poured into private corporations. In Drawing the Line, Andrew Stark takes a fresh and provocative look at how Americans debate the border between the public realm and the private. Are these arguments specific to policy and community, or do they reveal something bigger about politics and society?Having conduc.